2019
DOI: 10.1101/gr.247072.118
|View full text |Cite
|
Sign up to set email alerts
|

Two contrasting classes of nucleolus-associated domains in mouse fibroblast heterochromatin

Abstract: In interphase eukaryotic cells, almost all heterochromatin is located adjacent to the nucleolus or to the nuclear lamina, thus defining nucleolus-associated domains (NADs) and lamina-associated domains (LADs), respectively. Here, we determined the first genome-scale map of murine NADs in mouse embryonic fibroblasts (MEFs) via deep sequencing of chromatin associated with purified nucleoli. We developed a Bioconductor package called NADfinder and demonstrated that it identifies NADs more accurately than other pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
86
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 63 publications
11
86
1
Order By: Relevance
“…We sequenced approximately 50 million reads from each nucleolar and genomic DNA sample. We note that subsampling analyses of larger MEF datasets previously showed that the number of peaks detected had reached a plateau at this sequencing depth (Vertii et al 2019). Genomic reads were mostly uniformly distributed across the genome, whereas nucleolar reads contained well-defined peaks and valleys, with peaks overlapping known heterochromatic regions, such as constitutive LADs (cLADs) (Peric-Hupkes et al 2010) and late replicating regions (Hiratani et al 2010) (Fig 2A, B).…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…We sequenced approximately 50 million reads from each nucleolar and genomic DNA sample. We note that subsampling analyses of larger MEF datasets previously showed that the number of peaks detected had reached a plateau at this sequencing depth (Vertii et al 2019). Genomic reads were mostly uniformly distributed across the genome, whereas nucleolar reads contained well-defined peaks and valleys, with peaks overlapping known heterochromatic regions, such as constitutive LADs (cLADs) (Peric-Hupkes et al 2010) and late replicating regions (Hiratani et al 2010) (Fig 2A, B).…”
Section: Resultsmentioning
confidence: 60%
“…cLADs were previously defined as LADs that are lamina-associated in mESCs, and also in neural precursor cells (NPCs) and astrocytes differentiated from these mESCs (Peric-Hupkes et al 2010). Previous studies of NADs have identified frequent overlap of NADs with LADs (van Koningsbruggen et al 2010;Németh et al 2010;Dillinger et al 2017;Vertii et al 2019) and with late-replicating regions (Dillinger et al 2017;Vertii et al 2019), thus we concluded that the nucleolar reads are enriched with bona fide nucleolar heterochromatic regions in F121-9 mESCs.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations